Type VI Collagen Regulates Endochondral Ossification in the Temporomandibular Joint. (10th March 2022) - Komori, Taishi; Ji, Youngmi; Pham, Hai; Jani, Priyam; Kilts, Tina M.; Kram, Vardit; Li, Li; Young, Marian F.
ABSTRACT: For many years there has been a keen interest in developing regenerative treatment for temporomandibular joint–osteoarthritis (TMJ‐OA). Currently, there is no consensus treatment due to the limited self‐healing ability of articular cartilage and lack of understanding of the complex mechanisms regulating cartilage development in the TMJ. Endochondral ossification, the process of subchondral bone formation through chondrocyte differentiation, is critical for TMJ growth and development, and is tightly regulated by the composition of the extracellular matrix (ECM). Type VI collagen is a highly expressed ECM component in the TMJ cartilage, yet its specific functions are largely unknown. In this study, we investigated α2(VI)‐deficient ( Col6a2 ‐knockout [KO]) mice, which are unable to secret or incorporate type VI collagen into their ECM. Compared with wild‐type (WT) mice, the TMJ condyles of Col6a2 ‐KO mice exhibit decreased bone volume/tissue volume (BV/TV) and a larger bone marrow space, suggesting the α2(VI)‐deficient condyles have a failure in endochondral ossification. Differentiating chondrocytes are the main source of bone cells during endochondral ossification. Our study shows there is an increased number of chondrocytes in the proliferative zone and decreased Col10‐expressing chondrocytes in Col6a2 ‐KO cartilage, all pointing to abnormal chondrocyte differentiation and maturation. In addition, RNA sequencing (RNAseq) analysis identified distinct gene expression profiles related to cell cycle and ECM organization that were altered in the mutant condyles. These data also suggest that bone morphogenetic protein 2 (BMP2) activity was deregulated during chondrocyte differentiation. Immunohistochemical analysis indicated an upregulation of Col2 and Acan expression in Col6a 2‐KO cartilage. Moreover, the expression of pSmad1/5/8 and Runx2 was decreased in the Col6a2 ‐KO cartilage compared with WT controls. Taken together, our data indicate that type VI collagen expressed in the TMJ cartilage is important for endochondral ossification, possibly by modulating the ECM and altering/disrupting signaling pathways important for TMJ chondrocyte differentiation. Published 2022. This article is a U.S. Government work and is in the public domain in the USA. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.